The Ultraviolet Radiosensitivity of Oedogonium cardiacum Cells at Various Stages of the Cell Cycle - Parker, Kirsten E. (My University, 1969)
The ultraviolet radiosensitivity of synchronously growing O. cardiacum, was measured during the first generation cycle and compared to the radio sensitivity to ionizing radiation. Both radiosensitivity patterns were approximately the same in shape exhibiting a maximum resistance in S and a minimum in G2. Following x-radiation Do and n values varied with age by a factor of 7 and 40 respectively. In contrast following UV radiation Do varied by a factor of 2.5 and n remained essentially constant. A seasonal variation in the magnitude of the UV radiosensitivity was observed and is attributed to seasonal differences in UV cytoplasmic absorption . A complex survival curve was obtained at all cell ages and dose levels. An explanation for the shape of the complex curve involving cytoplasmic UV attenuation and the additive effects of UV-induced cytoplasmic damages at high dose levels is favoured. Preliminary investigations showed that photoreactivation does occur.
Title: The Ultraviolet Radiosensitivity of Oedogonium cardiacum Cells at Various Stages of the Cell Cycle, Author: Kirsten E. Parker, Location: Thode